2021
DOI: 10.1002/rmv.2321
|View full text |Cite
|
Sign up to set email alerts
|

Potential COVID‐19 therapeutic approaches targeting angiotensin‐converting enzyme 2; An updated review

Abstract: COVID-19 has spread swiftly throughout the world posing a global health emergency. The significant numbers of deaths attributed to this pandemic have researchers battling to understand this new, dangerous virus. Researchers are looking to find possible treatment regimens and develop effective therapies. This study aims to provide an overview of published scientific information on potential treatments, emphasizing angiotensin-converting enzyme II (ACE2) inhibitors as one of the most important drug targets. SARS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 230 publications
0
11
0
Order By: Relevance
“…As well as the development of inhibitors to slow viral replication, such as 3C-like proteases, papain-like protease, and angiotensin-converting enzyme II, immunosuppressive treatments may be useful in preventing the cytokine storm in the later stages of COVID-19, a major cause of patient death. 1 , 2 , 3 , 4 In this study, we focused on identifying potential prophylaxes for SARS-CoV-2 infection, specifically an immune-enhancing compound derived from natural products. Immune-enhancing compounds are generally classified as those capable of enhancing the non-specific immune system response by promoting the activity of phagocytes such as neutrophils and macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…As well as the development of inhibitors to slow viral replication, such as 3C-like proteases, papain-like protease, and angiotensin-converting enzyme II, immunosuppressive treatments may be useful in preventing the cytokine storm in the later stages of COVID-19, a major cause of patient death. 1 , 2 , 3 , 4 In this study, we focused on identifying potential prophylaxes for SARS-CoV-2 infection, specifically an immune-enhancing compound derived from natural products. Immune-enhancing compounds are generally classified as those capable of enhancing the non-specific immune system response by promoting the activity of phagocytes such as neutrophils and macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…By using hyaluronic acid-poly (ethylenimine) (HA-PEI)-based nanoparticles with encapsulated miR-125b to target CD44, Parayath et al (2018) demonstrated macrophage-specific delivery and transfection after intraperitoneal administration. The miR-125b transfectants increased the ratio of M1 to M2 macrophages by > 6 fold as well as iNOS (M1 marker) and Arg-1 (M2 marker) ratios in TAMs by 300 fold over the untreated controls, indicating the successful repolarization of TAMs in a KRAS/p53 double mutant genetically engineered NSCLC mouse model and naïve mice through the intraperitoneal administration of macrophagespecific HA-PEI nanoparticles in their lung tissues as a promising strategy in anticancer immunotherapy (Gharavi et al, 2022;Zanganeh et al, 2022). Other viral vectors have also been used as a nanotechnology tool for immunotherapy against cancer.…”
Section: Nanoparticles In Lung Cancer Immunotherapymentioning
confidence: 99%
“…After acidification of the endosome and fusion of viral and lysosomal membranes, 41 encapsidated viral RNA is released to the cytoplasm for replication and transcription. 26 , 42 , 43 Complementary to this, SARS‐CoV‐2 may utilise CD147‐mediated endocytosis for cell entry, 44 and pro‐protein convertase furin (PCF) might also play a role in endocytic pathways.PCF is essential for the propagation of numerous viruses by cleavage of viral envelope glycoproteins, which may also involve the endocytosis of SARS‐CoV‐2. 45 Due to the expression of ACE2 and CD147 and other plausible receptors in the circumventricular organs of CNS, glial cells, and neurons, 30 , 31 , 46 , 47 SARS‐CoV‐2 can potentially invade the nervous system, which leads to neurological manifestations.…”
Section: Mechanism Of Cellular Viral Infectionmentioning
confidence: 99%
“…Subsequently, TMPRSS2, which activates and cleaves S protein, 25,28,29 is activated for S priming, and then the SARS‐CoV‐2/ACE2 complex undergoes endocytosis and forms an endosome. After acidification of the endosome and fusion of viral and lysosomal membranes, 41 encapsidated viral RNA is released to the cytoplasm for replication and transcription 26,42,43 . Complementary to this, SARS‐CoV‐2 may utilise CD147‐mediated endocytosis for cell entry, 44 and pro‐protein convertase furin (PCF) might also play a role in endocytic pathways.PCF is essential for the propagation of numerous viruses by cleavage of viral envelope glycoproteins, which may also involve the endocytosis of SARS‐CoV‐2 45 .…”
Section: Mechanism Of Cellular Viral Infectionmentioning
confidence: 99%